2023
DOI: 10.1101/2023.11.09.566460
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic Responses of Striatal Cholinergic Interneurons Control the Extinction and Updating of Goal-Directed Learning

Zhenbo Huang,
Ruifeng Chen,
Matthew Ho
et al.

Abstract: Striatal cholinergic interneurons (CINs) regulate behavioral flexibility, but their exact contribution to this process remains elusive. In this study, we report that extinction learning enhances acetylcholine (ACh) release. Mimicking this enhancement by optogenetically inducing CIN burst firing promotes extinction learning. CINs receive excitatory thalamic inputs, and we observed that extinction training augmented thalamic activity. Optogenetically stimulating these thalamic inputs caused CIN burst firing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 85 publications
0
0
0
Order By: Relevance
“…Cholinergic interneurons (CINs) provide the main source of acetylcholine (ACh) to the striatum 1,2 . Selective manipulations in rodents have revealed potential roles for the CINs in different forms of behavioral flexibility, response suppression, and extinction, which vary by striatal subregion [3][4][5][6][7][8][9][10][11][12][13] . Measurements of CIN activity or ACh release in the striatum during behavior have focused extensively on dynamics to salient and reward associated sensory stimuli 14,15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cholinergic interneurons (CINs) provide the main source of acetylcholine (ACh) to the striatum 1,2 . Selective manipulations in rodents have revealed potential roles for the CINs in different forms of behavioral flexibility, response suppression, and extinction, which vary by striatal subregion [3][4][5][6][7][8][9][10][11][12][13] . Measurements of CIN activity or ACh release in the striatum during behavior have focused extensively on dynamics to salient and reward associated sensory stimuli 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistic studies in brain slices and anesthetized rodents have indicated that pauses in ACh release to conditioned cues which coincide with phasic DA release may promote associative learning by creating a permissive window for striatal synaptic plasticity on D1 receptor expressing striatal projection neurons [25][26][27] . Less is known about how endogenous ACh dynamics to cues or actions might support a role in behavioral flexibility, but there is some evidence that increases in ACh may weaken excitatory striatal synapses to facilitate extinction 9,13 . Functional heterogeneities in ACh signaling across striatal subregions have been difficult to assess due to the sparseness of CINs in the striatum (~3-5% of total population) and inherent limitations in spatial coverage of current optical and electrophysiological approaches.…”
Section: Introductionmentioning
confidence: 99%